COMPARISON OF INTERFERENCE IN 4 JAFFE CREATININE ASSAYS USING ACUTE DIABETIC KETOACIDOSIS SAMPLES. (February 2015) - Abdul-Wahab, Azni; Chiriano, Angela; Lim, Chen; Lam, Que; Choy, Kay Weng; Mitchell, David; Wijeratne, Nilika; Mohr, Malcolm; Chiang, Cherie
Abstract : Background and aim: Creatinine assays are now standardised, however the effect of elevated glucose and ketoacids during acute diabetic ketoacidosis (DKA) on different Jaffe creatinine assays is unknown. We aim to assess this interference on different platforms using the Vitros enzymatic creatinine method as the gold standard. Methods: Samples were collected from patients presenting to Emergency Department with DKA and analysed using 4 Jaffe assays (Architect, Roche, Beckman Coulter and Siemens) and 1 enzymatic assay (Vitros). Results: Of the eighteen patients (12 M, 6F, age 32.1 ± 12.4 years), admission pH was 7.12 ± 0.16, HCO3 was 8.2 ± 4 mmol/L, glucose was 36.2 ± 13.8 mmol/L and capillary ketone was 5.7 ± 1.2 mmol/L. The average enzymatic creatinine value was 115.3 ± 64.2 μmol/L. All Jaffe creatinine results were significantly higher ( p < 0.001), in order of magnitude: Architect (156.5 ± 64.7), Beckman (147.2 ± 69.1), Siemens (131.4 ± 57.7) and Roche (127.2 ± 57.5). Discussion: Falsely elevated plasma creatinine results might delay the administration of intravenous potassium in DKA patients and clinicians need to be aware of this potential interference which appeared most marked on the Abbott platform.